Ectopic Nasal Tooth as a source of Epistaxis –A Case Report - B, Sharma B; S, Sharma; JD, Sharma; KD, Sharma; J, Kaur (Indian Journal of Case Reports, 2016)
Nasal teeth are ectopic location of teeth which can present with variety of symptomatology and remains undiagnosed for many years. This can be diagnosed radiologically when patient undergoes Computerized Tomography (CT) for the nasal sinuses for some of the complaints related to this etiology. We report such case of 40-years old lady who attended outpatient department with complaint of epistaxis. Plain CT of Para Nasal Sinuses (PNS) clinched the diagnosis.